2019
DOI: 10.1111/tbj.13369
|View full text |Cite
|
Sign up to set email alerts
|

State of art of advanced triple negative breast cancer

Abstract: Advanced triple negative breast cancer (TNBC) is an aggressive disease (high probability of visceral metastasis) with poor outcome. Triple negative breast cancer is characterized by lack of expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor‐2 (HER2), high histologic grade, and high mitotic rate. Chemotherapy remains the primary systemic treatment, with international guidelines supporting the use of single‐agent taxanes (with or without bevacizumab) or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…Some studies have also demonstrated the effectiveness of combining chemotherapy with bevacizumab (monoclonal anti-vascular endothelial growth factor antibody) or with atezolizumab (monoclonal anti-programmed death ligand 1 (PD-L1) antibody) for metastatic TNBC. In addition to first-line therapy, there are still other options, such as the use of polyadenosine diphosphate-ribose polymerase (PARP) inhibitors, such as olaparib and talazoparib [62], and through immunotherapy, which includes pembrolizumab (humanized monoclonal antibody (mAb) against programmed cell death protein 1 (PD-1)) [63,64] and avelumab (human mAb against PD-L1), also for patients with metastatic TNBC [65].…”
Section: Bc Subtypesmentioning
confidence: 99%
“…Some studies have also demonstrated the effectiveness of combining chemotherapy with bevacizumab (monoclonal anti-vascular endothelial growth factor antibody) or with atezolizumab (monoclonal anti-programmed death ligand 1 (PD-L1) antibody) for metastatic TNBC. In addition to first-line therapy, there are still other options, such as the use of polyadenosine diphosphate-ribose polymerase (PARP) inhibitors, such as olaparib and talazoparib [62], and through immunotherapy, which includes pembrolizumab (humanized monoclonal antibody (mAb) against programmed cell death protein 1 (PD-1)) [63,64] and avelumab (human mAb against PD-L1), also for patients with metastatic TNBC [65].…”
Section: Bc Subtypesmentioning
confidence: 99%
“…Triple-negative breast cancer (TNBC) accounts for about 20% of BC cases (2). TNBC is a distinct subtype of BC characterized by aggressive phenotype, high recurrence rates, high visceral metastasis rate, and worse outcomes (3)(4)(5). Molecular heterogeneity is prominent in the TNBC subtype, and is reflected by the obvious prognostic and patient's sensitivity to chemotherapy treatment, which is the only available systemic therapy currently (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, %10-20 of BC cases are ER-and give no signi cant response against hormonal or targeted therapy. Although surgery, radiotherapy and chemotherapy (olaparib, Talzenna, atezolizumab) combinations preferred for ER-BCs treatment, still new therapeutic agents needed to develop for triple negative breast cancer (TNBCs) therapy [3].…”
Section: Introductionmentioning
confidence: 99%